2023
DOI: 10.1093/jisesa/iead019
|View full text |Cite|
|
Sign up to set email alerts
|

Isolation and characterization of gut bacteria associated with the degradation of host-specific terpenoids in Pagiophloeus tsushimanus (Coleoptera: Curculionidae) larvae

Abstract: Insect intestinal bacteria play an important role in resisting defensive substances of host plants. Pagiophloeus tsushimanus (Coleoptera: Curculionidae) feeds exclusively on camphor trees (Cinnamomum camphora, Laurales: Lauraceae) in China, causing substantial economic and ecological losses. It is unclear how the larvae of P. tsushimanus outcome the main secondary metabolites of C. camphora such as D-camphor, eucalyptol, and linalool. In this study, we isolated terpenoid-degrading bacteria from the gut of P. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Relevant studies have reported that Pantoea can exert a negative impact on aphid hosts as a pathogenic bacterium . Furthermore, infection with Asaia resulted in a shorter nymphal duration and increased adult body weight in the white-backed planthopper, while infection with Weissella played a crucial role in enhancing the adaptability of host insects. , Recent findings show that Corynebacterium from the gut of the leaf beetle Pagiophloeus tsushimanus degrades plant terpenoid secondary metabolites, enhancing insect adaptability on host plants . Moreover, Actinobacteria produce antifungal compounds, reinforcing the defensive association between these microorganisms and host insects .…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies have reported that Pantoea can exert a negative impact on aphid hosts as a pathogenic bacterium . Furthermore, infection with Asaia resulted in a shorter nymphal duration and increased adult body weight in the white-backed planthopper, while infection with Weissella played a crucial role in enhancing the adaptability of host insects. , Recent findings show that Corynebacterium from the gut of the leaf beetle Pagiophloeus tsushimanus degrades plant terpenoid secondary metabolites, enhancing insect adaptability on host plants . Moreover, Actinobacteria produce antifungal compounds, reinforcing the defensive association between these microorganisms and host insects .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, P . aeruginosa had demonstrated the capability to degrade linalool, which was isolated from Pagiophloeus tsushimanus ( Qiao et al, 2023 ). Additionally, Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…may play a role in the degradation of secondary metabolites in host plant, which were associated with defense substances specific to the host plant. For instance, P. aeruginosa had demonstrated the capability to degrade linalool, which was isolated from Pagiophloeus tsushimanus (Qiao et al, 2023). Additionally, Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%